Ablation of the creA regulator results in amino acid toxicity, temperature sensitivity, pleiotropic effects on cellular development and loss of virulence in the filamentous fungus Beauveria bassiana. (7th January 2014) - Luo, Zhibing; Qin, Yuqi; Pei, Yan; Keyhani, Nemat O.
Summary For most organisms, carbon and nitrogen uptake are essential for growth, development and, where applicable, pathogenesis. The role of the carbon catabolite repressor transcription factor homologue BbcreA in the entomopathogenic fungus Beauveria bassiana was investigated. Deletion of BbcreA resulted in pleiotropic effects, including nutrient toxicity, leading to a novel cell lytic phenotype. Fungal growth in rich media and minimal media containing select amino acids/peptides was severely compromised, with microscopic examination revealing conidial‐base germ tube degeneration and cell lysis occurring during growth, a phenomenon exacerbated at higher temperatures (32°C). Depending upon nutrient conditions, growth, pigment and aerial mycelium production, sporulation and dimorphic transition to blastospore production were also impaired in the ΔBbcreA strain. Although loss of BbcreA resulted in de‐repression of secreted protease and lipase, enzymes critical in mediating pathogenesis, insect bioassays indicated severe defects in virulence using both topical and intra‐haemocoel injection assays, with eruption and subsequent sporulation on host cadavers greatly reduced in the mutant. These data suggest that BbcreA functions as more than a carbon repressor and plays important roles in nutrient utilization, cell homeostasis and virulence. In particular, BbcreA is required for proper assimilation of select amino acids and peptides, including asparagine, arginine and proline.